2018
DOI: 10.1002/jlb.4ta0817-317r
|View full text |Cite
|
Sign up to set email alerts
|

New flow cytometry-based method for the assessment of the antibacterial effect of immune cells and subcellular particles

Abstract: Techniques currently used for assessment of bacterial count or growth are time-consuming, offer low throughput, or they are complicated or expensive. The aim of the present work was to elaborate a new method that is able to detect the antibacterial effect of cells, subcellular particles, and soluble compounds in a fast, cost, and labor effective way. Our proposed technique is based on flow cytometry (FC) optimized for detection of small particles and on fluorescently labeled bacteria. It allows direct determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…At the end, initial bacterial counts were calculated indirectly using an equation similar to PCR calculation, as described previously (28). We also confirmed the results with our previously described flow cytometry based bacterial survival assay (22).…”
Section: Bacterial Survival Assaysupporting
confidence: 76%
See 1 more Smart Citation
“…At the end, initial bacterial counts were calculated indirectly using an equation similar to PCR calculation, as described previously (28). We also confirmed the results with our previously described flow cytometry based bacterial survival assay (22).…”
Section: Bacterial Survival Assaysupporting
confidence: 76%
“…Resting, non-activated or apoptotic PMNs produce anti-inflammatory EVs and on the other edge if PMNs face the natural enemy the opsonized pathogen, they produce pro-inflammatory EVs that increase the ROS and IL-8 production of resting PMNs and IL-8 secretion of HUVEC cells (16). We and others also demonstrated that EVs issued from opsonized particle activated cells (aEV) had a definitive dose-dependent antibacterial effect (13,22,23). We proposed Mac-1 integrin as key factor in switching anti-inflammatory EV generation into production of pro-inflammatory and antibacterial EVs through tyrosine kinase activation and calcium signal (17,24).…”
Section: Introductionmentioning
confidence: 93%
“…Bacterial growth was followed as changes in OD using a shaking microplate reader (Labsystems iEMS Reader MF, Thermo Scientific) for 8 h, at 37°C, at 650 nm. After the end of growth phase, the initial bacterial counts were calculated indirectly using an equation similar to PCR calculation, as described previously [17].…”
Section: Bacterial Survival Assaymentioning
confidence: 99%
“…In our previous work, we showed that stimulation of neutrophilic granulocytes (PMN) with opsonized particles (bacteria or zymosan A) triggered the formation of large amount of medium-sized EVs enriched in granule proteins. EVs issued from activated cells had a definitive dose-dependent antibacterial effect and were named "aEV"s [ 17,18]. Binding of bacteria and prevention of their proliferation were also observed with EVs derived from peripheral blood mononuclear cells upon bacterial stimulation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were re-measured after a 2fold dilution to control linearity of measurements. Linearity was controlled in a broader range previously (32). FC data were analyzed with Flowing 2.5 Software (Turku Center for Biotechnology, Finland).…”
Section: Ev Analysis and Quantification By Flow Cytometrymentioning
confidence: 99%